Optimization of water use in summer rice through drip irrigation - SONIT, ANAMIKA; ., HEMLATA; RATHORE, A. L.; SINHA, JITENDRA; KATRE, P. (Journal of Soil and Water Conservation, 2021)
The experiment was conducted at Research Farm, IGKV, Raipur (C.G.) during summer season 2013. Treatment consisted of two rice varieties (MTU1010 and IR64) as main plots and five drip irrigations (0.6, 0.8, 1.0, 1.2 and 1.4 IW: CPE (irrigation water and cumulative pan evaporation ratio), micro sprinkler irrigation once in three days and flooding as sub plots. The maximum seed yield was recorded in drip irrigation at 1.4 IW: CPE ratio which was at par with traditional flooding. Water use efficiency in all the drip irrigation treatments (1.0, 1.2 and 1.4 IW: CPE ratio) was in the range of 2.5-2.9 kg/ha mm whereas it was 0.11 kg/ha mm in flooding. Net return and B:C ratio were significantly higher in drip irrigation at 1.2 and 1.4 IW:CPE ratio than other treatments. It can be concluded that drip irrigation (1.2 and 1.4 IW:CPE ratio) is superior to flooding for summer rice in relation to (i) water use efficiency, and (ii) harvest attractive seed yield and income.